Determinación de estrategias de marketing para la comercialización de los productos de linea blanca en la empresa Artefacta de la ciudad de Loja. - Cueva Pacheco, José Antonio (2013)
This research paper titled, "Determining MARKETING STRATEGIES FOR THE MARKETING OF PRODUCTS IN APPLIANCES COMPANY CITY artefacta LOJA", I conducted according to the objectives and are subject to the General Rules Graduation at the National University of Loja before obtaining the degree in Commercial Engineering. This research includes: Summary, which corresponds to a summary of the relevant parts of the thesis, the Introduction, this highlights the importance of the research topic, in which you will have a comprehensive understanding of all the work done, the Review of literature itself that serves as the basis of theoretical basis to analyze and identify strategies to be applied, this includes references containing theoretical contexts about marketing strategies and concepts and importance of the most used in the present work, also Materials and Methods comments which are detailed in the methods, techniques and procedures used for this research. The results of the primary data, which is part detailing the internal and external analysis of the company "artefacta" in areas such as history, organizational structure, distribution, system and method of customer service, level of training of employees, management and management leadership, satisfaction of customers, suppliers, products offered, prices and more. Based on the results follows a discussion or analysis of the primary outcomes, systematizing the information obtained to draw conclusions and propose alternatives or marketing strategies to improve business performance Artefacta. Finally we note the most important findings of the investigation with their recommendations, described the most important situations obtained during the application of analysis of all the research work both as primary information and surveys as the SWOT analysis which determines the strengths and weaknesses of both internal and external, for the latter had the necessary information Artefacta company, same that was provided by the Manager and staff working on it. Bibliography, is the part where you have to know the sources of information used in the development of this work and are last Annexes. This study aims to determine marketing strategies for the marketing of white goods company Artefacta city of Loja, likewise additionally: Make a diagnosis to the company to determine whether to apply marketing strategies. Perform External diagnostics Company. Develop proposals to provide solutions to the problems in part if any. Use the SWOT tool to determine the objectives and marketing strategies. Investigate the company's customers to determine the marketing mix. According to the results obtained in the competitive profile matrix, we have about the company artefacta from competition, is in second place with a score of 3.10, while the gangue company ranks first with a score of 3.79 and the company MARCIMEX is in third place with a score of 2.82.Con this we conclude, that despite being an established company in the town, artefacta is in a good competitive position, as was the acceptance market. Being best success factors economic prices of their products, image, location and customer service strengths considered higher with a grade of 4. As presented lower strengths: product quality, competitiveness, promotions, and logo. All these with a rating of 3. On the other hand, as weak retail company have a lack of creativity, knowledge of suppliers, and is also the lack of publicity is essentially communicate and motivate consumers with compelling and reasonable arguments about whether to acquire the mercadocon goods offered in a rating of 2. As for the bargain, which is its biggest competitor presents as major strengths, product quality, promotions, advertising, logo, suppliers, creativity, the company relative prices and customer service unlike the other with a rating of 4. As minor strengths image, competitiveness, and location of the company, they have a score of 3. No major weaknesses. MARCIMEX is stronger promotions with a score of 4. While as lower strengths include: image, marketing, suppliers, creativity, prices on the company, location and customer service with a score of 3. As minor weakness is product quality, competitiveness, and company logo. With a score of 2. No major weaknesses .From the results obtained in the present work, a internal and external analysis of the company improvement strategies determined to be the case authorities take appropriate corrective measures and better decisions in favor of increasing not only the quality of the services and products and in turn also conducted a study of the four P.